City of Bones : the shadowhunter chronicles - Clare, Cassandra (The mortal instruments, 2015)
Love. Blood. Betrayal. Clary Fray is seeing things: vampires in Brooklyn and werewholves in Manhattan. Irresistibly drawn to the Shadowhunters, a secret cadre of warriors dedicated to ridding the world of demons, Clary encounters the dark side of New York City - and the dangers of forbidden love.